Surgical site infections: surgical reoperation and infection in clean and potentially contaminated surgeries - Stefani, Larissa (2022)
Objective: to verify the association between the occurrences of surgical site infection (SSI) and the need for re-approach in patients undergoing clean and potentially contaminated surgeries. Method: longitudinal study, involving 75 patients with infection; data collection was carried out using a survey form evaluating sociodemographic and clinical aspects. The association was assessed by the odds ratio and its confidence intervals (95%CI). Results: patients hospitalized for external causes are four times more likely to be surgically re-approached (p=0.011), in the orthopedic specialty the reason was five times greater (p=0.003), readmissions are 10 times more likely to be re-approached (p=0.000), leukocytosis (p=0.002) and alteration in the value of c-reactive protein (p=0.016) were associated with the need for a new surgery. Positive culture (p=0.001) and therapeutic antibiotic (p=0.04) proved to be protective factors for re-approach. Conclusion: the data demonstrate the presence of SSI as a strong influencer in surgical reoperation, guiding hospitals with the same profile.